Factors Associated with Maternal Deaths in District and Upazila Hospitals of Bangladesh - Halim, Abdul; Biswas, Animesh; Md Abdullah, Abu Sayeed; Rahman, Fazlur (Bangladesh Journal of Obstetrics & Gynaecology, 2017)
Objective(s): Aim of the study was to use death review to explore medical causes and three delay causal factors responsible for maternal deaths in district or below level health facilities of Bangladesh. Methods: Government health workers conducted facility based death review in 56 maternal deaths occurred during 2010-2012 in four district and five upazila (EmONC) health facilities of Bangladesh. The data was analyzed to assess the causal relationship between the medical causes and the three delays factors in maternal mortality. Results: Majority of the mothers died was young (89.3%; below age 30 years) and died during first pregnancy (78.6%) and postpartum period (71.4%). Postpartum hemorrhage and preeclampsia-eclampsia were the foremost causes of maternal deaths at district level facilities of Bangladesh. Seventy two percent of them arrived the hospitals in a travel time <2 hour from home or first care-centre when 88% of cases had an unstable general condition. 72% of them received treatment within one hour of admission in the hospital. The patients records reflected that only a few patients received life-saving interventions like blood transfusion, fundal message, and/or oxytocic in postpartum haemorrhage or magnesium sulphate in eclampsia. The study also observed a poor documentation in all the facilities, which was a challenge for death review. Conclusions: The study suggested improving quality of care and increasing availability of skills to manage the complicated cases in district and below level EmONC hospitals with focused interventions for postpartum haemorrhage and preeclampsia-eclampsia. The facility death review will be useful in identifying causal factors, the third delay factors and service gaps and to respond accordingly to avert similar deaths. Bangladesh J Obstet Gynaecol, 2016; Vol. 31(1) : 16-22